Monotherapy laser photocoagulation for diabetic macular oedema - Jorge, Eliane C. [UNESP]; Jorge, Edson N. [UNESP]; Botelho, Mayra [UNESP]; Farat, Joyce G. [UNESP]; Virgili, Gianni; El Dib, Regina [UNESP] (Wiley, 2018)
Background: Diabetic macular oedema (DMO) is a complication of diabetic retinopathy and one of the most common causes of visual impairment in people with diabetes. Clinically significant macular oedema (CSMO) is the most severe form of DMO. Intravitreal antiangiogenic therapy is now the standard treatment for DMO involving the centre of the macula, but laser photocoagulation is still used in milder or non-central DMO. Objectives: To access the efficacy and safety of laser photocoagulation as monotherapy in the treatment of diabetic macular oedema. Search methods: We searched CENTRAL, which contains the Cochrane Eyes and Vision Trials Register; MEDLINE; Embase; LILACS; the ISRCTN registry; ClinicalTrials.gov and the WHO ICTRP. The date of the search was 24 July 2018. Selection criteria: We included randomised controlled trials (RCTs) comparing any type of focal/grid macular laser photocoagulation versus another type or technique of laser treatment and no intervention. We did not compare laser versus other interventions as these are covered by other Cochrane Reviews. Data collection and analysis: We used standard methodological procedures expected by Cochrane. Our primary outcomes were gain or loss of 3 lines (0.3 logMAR or 15 ETDRS letters) of best-corrected visual acuity (BCVA) at one year of follow-up (plus or minus six months) after treatment initiation. Secondary outcomes included final or mean change in BCVA, resolution of macular oedema, central retinal thickness, quality of life and adverse events, all at one year. We graded the certainty of the evidence for each outcome using the GRADE approach. Main results: We identified 24 studies (4422 eyes). The trials were conducted in Europe (nine studies), USA (seven), Asia (four) and, Africa (one), Latin America (one), Europe-Asian (one) and Oceania (one). The methodological quality of the studies was difficult to assess as they were poorly reported, so the predominant classification of bias was unclear. At one year, people with DMO receiving laser were less likely to lose BCVA compared with no intervention (risk ratio (RR) 0.42, 95% confidence interval (CI) 0.20 to 0.90; 3703 eyes; 4 studies; I2 = 71%; moderate-certainty evidence). There were also favourable effects observed at two and three years. One study (350 eyes) reported on partial or complete resolution of clinically significant DMO and found moderate-certainty evidence of a benefit at three years with photocoagulation (RR 1.55, 95% CI 1.30 to 1.86). Data on visual improvement, final BCVA, central macular thickness and quality of life were not available. One study related minor adverse effects on the central visual field and another reported one case of iatrogenic premacular fibrosis. Nine studies compared subthreshold versus standard macular photocoagulation (517 eyes). Subthreshold treatment was achieved with different methods of photocoagulation: non-visible conventional (two studies), micropulse (four) or nanopulse (one). Only one small study (29 eyes) reported on improvement or worsening of BCVA and estimates were very imprecise (improvement: RR 0.31, 95% CI 0.01 to 7.09; worsening: RR 0.93, 95% CI 0.15 to 5.76; very low-certainty evidence). All studies reported on continuous BCVA at one year; there was low-certainty evidence of no important difference between subthreshold and standard photocoagulation (mean difference (MD) in logMAR BCVA -0.02, 95% CI -0.07 to 0.03; 385 eyes; 7 studies; I2 = 42%), and were possibly different for different techniques (P = 0.07 and I2 = 61.5% for subgroup heterogeneity), with better results achieved with micropulse photocoagulation (MD -0.08 logMAR, 95% CI -0.16 to 0.0) as compared to the results achieved with nanopulse (MD 0.0 logMAR, 95% CI -0.06 to 0.06) and non-visible conventional (MD 0.04 logMAR, 95% CI -0.03 to 0.11), all of them compared to the standard lasers. One study reported partial to complete resolution of macular oedema at one year. There was low-certainty evidence of some benefit with standard photocoagulation, but estimates of effect were imprecise (RR 0.47, 95% CI 0.21 to 1.03; 29 eyes; 1 study). Studies also reported on the change in central macular thickness at one year and found moderate-certainty evidence of no important difference between subthreshold and standard photocoagulation (MD -9.1 μm, 95% CI -26.2 to 8.0; 385 eyes; 7 studies; I2 = 0%). There were no important adverse effects recorded in the studies. Nine studies compared argon laser versus another type of laser (997 eyes). There was moderate-certainty evidence of a small reduction or no difference between the interventions, with respect to improvement (RR 0.87, 95% CI 0.62 to 1.22; 773 eyes; 6 studies) and worsening of BCVA (RR 0.83, 95% CI 0.57 to 1.21; 773 eyes; 6 studies). Three studies reported few cases of subretinal fibrosis and neovascularization with argon laser and one study found subretinal fibrosis in the krypton group. One study (323 eyes) compared the modified ETDRS (mETDRS) grid technique with the mild macular grid (MMG), which uses mild, widely spaced burns throughout the macula. There was low-certainty evidence of an increased chance of visual improvement with MMG, but the estimate was imprecisely measured and the CIs include an increased risk or decreased risk of visual improvement at one year (RR 1.43, 95% CI 0.56 to 3.65; visual worsening: RR 1.40, 95% CI 0.64 to 3.05; change of logMAR visual acuity: MD -0.04 logMAR, 95% CI -0.01 to 0.09). There was a more significant reduction of central macular thickness with the mETDRS compared to the MMG technique (MD -34.0 μm, -59.8 to -8.3) in the MMG group. The study did not record important adverse effects. Authors' conclusions: Laser photocoagulation reduces the chances of visual loss and increases those of partial to complete resolution of DMO compared to no intervention at one to three years. Subthreshold photocoagulation, particularly the micropulse technique, may be as effective as standard photocoagulation and RCTs are ongoing to assess whether this minimally invasive technique is preferable to treat milder or non-central cases of DMO.